New innovation integrates water resources management in Cambodia’s Tonle Sap floodplain and Mekong delta - De Silva, Sanjiv; Sithirith, Mak; Sok, Sao (CGIAR System Organization, 2025)
A new short film from the CGIAR Initiative on Asian Mega-Deltas and the CGIAR Initiative on Aquatic Foods documents work to support efforts in Cambodia to delegate the management of water, land, agriculture, fisheries and the environment to the district level. WorldFish, IWMI and IFReDI remain committed to working with the Cambodian government and other stakeholders to support the D-TWG move from planning to plan implementation in 2025.